2017
DOI: 10.3390/s17051108
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks as Active Materials in Electronic Sensor Devices

Abstract: In the past decade, advances in electrically conductive metal–organic frameworks (MOFs) and MOF-based electronic devices have created new opportunities for the development of next-generation sensors. Here we review this rapidly-growing field, with a focus on the different types of device configurations that have allowed for the use of MOFs as active components of electronic sensor devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
182
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 229 publications
(183 citation statements)
references
References 54 publications
0
182
0
1
Order By: Relevance
“…In the sensing field, luminescent MOF‐based sensors have attracted great attention for a long time because these MOFs can indicate clear luminescent enhancement or quenching in response to different guest species, such as small molecules (amines, volatile organic compounds, explosive compounds, and so on), metal cations, and anions . However, the exploration of MOFs as electronic or optoelectronic sensors is still in its infancy and limited examples have been described . The main reason is that most MOFs have intrinsically low electrical and proton conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the sensing field, luminescent MOF‐based sensors have attracted great attention for a long time because these MOFs can indicate clear luminescent enhancement or quenching in response to different guest species, such as small molecules (amines, volatile organic compounds, explosive compounds, and so on), metal cations, and anions . However, the exploration of MOFs as electronic or optoelectronic sensors is still in its infancy and limited examples have been described . The main reason is that most MOFs have intrinsically low electrical and proton conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are still some exciting research results being reported. In recent years, two interesting review articles have highlighted MOF‐based electrochemical sensors . This motivates us to further explore more MOFs as sensitive electrochemical devices for sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…The modulation and control of the shape and size of the cavities is a key aspect to designing MOFs with tailored properties, for applications in gas storage and separation [3,4], water adsorption [5], energy storage [6,7], catalysis [8,9], sensors [10,11], biomedicine [12,13], or for combining several properties in the same MOF [14].…”
Section: Introductionmentioning
confidence: 99%
“…Guest molecules may cause structural variation, 8,9 tune electrical conductivity, 10,11 induce spin state transitions, 12,13 modulate luminescence wavelength, 14,15 and even participate in guest-guest interactions. 16 These phenomena are of fundamental interest and form the basis of various applications including chemiresistive sensors, 11,17,18 fluorescence sensors, 19 and cooperative adsorption. 13,16 Although several strategies are effective for increasing the electrical conductivity in MOFs, 20,21 among the most promising, and certainly more tractable synthetically, are those that involve post-synthetic doping.…”
Section: Introductionmentioning
confidence: 99%